Quanto studio per cessare di essere se stessi. : Le tracce del postumano nel teatro di Ermanna Montanari - Sciotto, Marco (Scenari, 2021)
A reflection about an experience such as that of Teatro delle Albe – the group created in Ravenna in 1983 by Marco Martinelli and Ermanna Montanari with Luigi Dadina and Marcella Nonni, a group which over the years has become one of the most important experiences in contemporary theatre – that doesn’t declare its debt to posthuman but at the same time shows it in practice, in a radical and almost inconscious way, is probably the privileged point of view to observe the transformative possibilities of posthuman instances, in their interaction with theatre. A medium with a history that has shown, in both East and West, different moments joined by a perception of human dimension as a limit to overstep. In particular, the connections between Teatro delle Albe’s work and posthuman seem to concern some questions such as the constant loss of centrality of the individual according to an opening to the alterity, the hybridization between human and machine, the overcoming of the human dimension and a certain relation with animality and with a sort of “becoming-animal”. Arriving at their last work which presents the sole Ermanna Montanari on stage, fedeli d’Amore, as a perfect condensation and point of arrival of all these paths, with a further reference to a posthuman idea of death.